Increased Endogenous GDNF in Mice Protects Against Age-Related Decline in Neuronal Cholinergic Markers - Mitra, Sumonto; Turconi, Giorgio; Darreh-Shori, Taher; Mätlik, Kärt; Aquilino, Matilde; Eriksdotter, Maria; Andressoo, Jaan-Olle (Frontiers in Aging Neuroscience, 2021)
Gradual decline in cholinergic transmission and cognitive function occurs during normal aging, whereas pathological loss of cholinergic function is a hallmark of different types of dementia, including Alzheimer’s disease (AD), Lewy body dementia (LBD), and Parkinson’s disease dementia (PDD). Glial cell line-derived neurotrophic factor (GDNF) is known to modulate and enhance the dopamine system. However, how endogenous GDNF influences brain cholinergic transmission has remained elusive. In this study, we explored the effect of a two-fold increase in endogenous GDNF (Gdnf hypermorphic mice, Gdnfwt/hyper) on cholinergic markers and cognitive function upon aging. We found that Gdnfwt/hyper mice resisted an overall age-associated decline in the cholinergic index observed in the brain of Gdnfwt/wt animals. Biochemical analysis revealed that the level of nerve growth factor (NGF), which is important for survival and function of central cholinergic neurons, was significantly increased in several brain areas of old Gdnfwt/hyper mice. Analysis of expression of genes involved in cholinergic transmission in the cortex and striatum confirmed modulation of cholinergic pathways by GDNF upon aging. In line with these findings, Gdnfwt/hyper mice did not undergo an age-related decline in cognitive function in the Y-maze test, as observed in the wild type littermates. Our results identify endogenous GDNF as a potential modulator of cholinergic transmission and call for future studies on endogenous GDNF function in neurodegenerative disorders characterized by cognitive impairments, including AD, LBD, and PDD.